Effectiveness of Implementing Sustainable Development in The Context of Natural Resource Management and Environmental Protection - Wildan Alfa Sina (Proceeding International Conference Restructuring and Transforming Law, 2024)
Sustainable development is a development paradigm that places a balance between economic growth, environmental protection and social justice as the main foundation. This research aims to evaluate the effectiveness of implementing sustainable development in the context of natural resource management and environmental protection. The research methods used involve analysis of policy documentation, interviews with stakeholders, and field surveys. The research results show that the implementation of sustainable development has not been fully effective in achieving the goals of natural resource management and environmental protection. Even though there are policies that support the principles of sustainable development, there are still obstacles in their implementation, such as a lack of coordination between agencies, minimal community participation, and a shortage of human resources. The importance of building synergy between the government, private and community sectors is the key to increasing the effectiveness of implementing sustainable development. This research also recommends the need to strengthen the role of communities in decision making, implement environmentally friendly technology, and increase human resource capacity at the local level. By improving the coordination system and increasing active community participation, it is hoped that the implementation of sustainable development can be more effective in managing natural resources and protecting the environment, thereby realizing sustainable and balanced development for future generations.